5G-Enabled Industrial IoT Networks - Ghosh, Amitabha (Amitava) (Artech House, 2022)
This one-of-a-kind book gives you an exclusive look into how the "Industrial Internet of Things" (IIoT) convergence with the 5G end-to-end network is driving the 4th industrial revolution and bringing about game-changing developments in multiple industries. The book shows you how 5G-driven IIoT networks can deliver optimal performance for all industrial applications using key LTE and 5G NR features, and helps you understand how IIoT with 5G can be used to automate factories and make them more cost efficient.Detailed chapters take you through the current knowledge available on this breakthrough technology and give you access to expert discussions on: key use cases and corresponding target requirements; IIoT standards and alliances; end-to-end architecture for IIoT; IIoT enablers for 5G new radio; performance of select IIoT use cases; and machine learning enabled IIoT networks.The book pulls together in one resource key cases and knowledge you need to fully understand how 5G enabled IIoT is transforming global industries. You will be conversant with the end-to-end technology enablers for IIoT, learn how 5G new radio features enhance the system performance of IIoT networks, and gain a deeper understanding of the role of machine learning in the IIoT revolution.With its international scope and focus on 5G IIoT networks and performance, this is an important read for global technology leaders in telecom and manufacturing industries, analysts and technical writers for various industry magazines and newspapers, telecom researchers, and anyone needing to understand the current state of the art in this rapidly developing technology.